BUSINESS MODEL IN ELECTRICITY INDUSTRY USING BUSINESS MODEL CANVAS APPROACH; THE CASE OF PT. XYZ - Achmad Arief Wicaksono; Rizal Syarief; Ono Suparno (School of Business, IPB University (SB-IPB), 2017)
The magnitude of opportunities and project values of electricity system in Indonesia encourages PT. XYZ to develop its business in electrical sector which requires business development strategies. This study aims to identify company's business model using Business Model Canvas approach, formulate business development strategy alternatives, and determine the prioritized business development strategy which is appropriate to the manufacturing business model for PT. XYZ. This study utilized a descriptive approach and the nine elements of the Business Model Canvas. Alternative formulation and priority determination of the strategies were obtained by using Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis and pairwise comparison. The results of this study are the improvement of Business Model Canvas on the elements of key resources, key activities, key partners and customer segment. In terms of SWOT analysis on the nine elements of the Business Model Canvas for the first business development, the results show an expansion on the power plant construction project as the main contractor, an increase in sales in its core business in supporting equipment industry of oil and gas, a development in the second business i.e. an investment in the electricity sector as an independent renewable emery-based power producer. On its first business development, PT. XYZ selected three Business Model Canvas elements which become the priorities of the company i.e. key resources weighing 0.252, key activities weighing 0.240, and key partners weighing 0.231. On its second business development, the company selected three elements to become their the priorities i.e. key partners weighing 0.225, customer segments weighing 0.217, and key resources weighing 0.215.Keywords: business model canvas, SWOT, pairwise comparison, business model